Successfully treating hand primary tuberculous synovitis by synovectomy combined antituberculous therapy: A case report. Issue 8 (February 2018) - Wang, Tao; Zhao, Gang; Rui, Yong-Jun; Mi, Jing-Yi
Abstract: Rationale: Primary tuberculous infection in hand and wrist is a rare disease. Few articles reported on hand primary tuberculous synovitis. Patient concerns: A 68-year-old Chinese male, without history of tuberculosis (TB), had complained of pain and swelling in right palm and little finger for 3 months. Patient came to our hospital on 9th Oct 2016. X-ray just showed soft tissue swelling in little finger. Magnetic resonance imaging (MRI) showed synovitis around flexor tendon of little finger, volar palm, and carpal tunnel. Notably, it also implied nodular images in little finger sizing 5 mm × 11 mm. Laboratory tests revealed C-reactive protein (CRP): 22 mg/L, erythrocyte sedimentation rate (ESR): 49 mm/h, and white blood cells (WBC): 11.8 × 10 9 /L. Diagnoses: He was diagnosed with primary hand tuberculous synovitis. Interventions: The patient received aspiration biopsy in right palm guided by ultrasound on 13rd Oct and pathological examination indicated Mycobacterium tuberculosis (MTB) infection. We performed radical synovetomy and collected abnormal tissue for pathological examination on 18th Oct. Finally, result showed MTB infection, which was the same with the result of first pathological examination. Then, this patient received antituberculous treatment. Outcomes: One year after operation, pain and swelling relieve and no recurrence of the clinical symptoms happened. Lessons: Primary tuberculous synovitis of hand and wrist is rare, MTB infection should be considered as an infectious agent, especially in developing countries. Radical synovectomy and antituberculous treatment regain a satisfactory outcome.